Subacute Degeneration of Fibers After Vertical Parasagittal Hemispherotomy - Hittinger, Markus; Hartlieb, Till; Heiland, Dieter Henrik; Heiland, Pamela; Pieper, Tom; Staudt, Martin; Berlis, Ansgar; Kudernatsch, Manfred; Mader, Irina (Clinical Neuroradiology, 2024)
Purpose: After vertical parasagittal hemispherotomy a restricted diffusion is often seen ipsilaterally and even distant from the adjacent resection margin. This retrospective cohort study analyses the anatomic site and the time course of the diffusion restriction after vertical parasagittal hemispherotomy. Methods: Fifty-nine patients were included into this study, all of them having had one pre-operative and at least one post-operative MRI, including diffusion imaging at b‑values of 0 and 1000 s/mm2 with a calculated ADC. Results: Diffusion restriction occurred exclusively on the operated site in all patients. In the basal ganglia, diffusion restriction was present in 37 of 38 patients at the first postoperative day with a duration of 38 days. In the midbrain, the posterior limb of the internal capsule and the thalamus, a restricted diffusion became postoperatively prominent at day 9 in all three localizations, with a duration of 36, 34 and 36 days, respectively. The incidence of thalamic lesions was lower if a preoperative damage had occurred. Conclusion: The restricted diffusion in the basal ganglia resembles direct effects of the operation at its edges, whereas the later appearing diffusion restriction in the midbrain and the posterior limb of the internal capsule rather belong to a degeneration of the descending fibers being transected by the hemispherotomy in the sense of a Wallerian degeneration. The presence of preoperative hemispheric lesions influences the development of diffusion restriction at subacute fiber degeneration.
CRIS-Team Scopus Importer:2024-07-05
Keywords: Diffusion restriction; Preoperative hemispheric lesions; Vertical parasagittal hemispherotomy; Wallerian degeneration